Giant Asymptomatic Submandibular Sialolith: A Case Report Accompanied by Systematic Review - Azevedo, Renato Gomes; Toro, Luan Felipe [UNESP]; Ganzaroli, Vinícius Franzão [UNESP]; Ifanger, Vinícius José; de Faria, Nathan Ayres; de Rezende, Rodrigo Ubiali; da Conceição Francisquini, Julia; Tessarin, Gestter Willian Lattari [UNESP] (MDPI, 2025)
BACKGROUND/OBJECTIVES: Salivary stones, also known as sialoliths, are calcified structures that develop within the salivary glands and/or their ducts. They occur in approximately 1 per 10,000 to 30,000 individuals per year, primarily affecting adults between 30 and 50 years of age. Although several hypotheses have been proposed, the exact mechanisms of formation and their predisposing factors are yet to be confirmed. The submandibular gland is the most commonly affected site, accounting for nearly 80% of cases, while giant and asymptomatic sialoliths are rare clinical findings in dental practice. This study is divided into two components: first, a case report of a giant, asymptomatic sialolith located in Wharton's duct; second, a systematic review of the literature to explore the clinical procedures, diagnoses, outcomes, and other relevant aspects of this pathology. METHODS: The case involved a 42-year-old woman who sought dental care due to the presence of a painless sublingual swelling. Intraoral examination and imaging revealed a calcified mass consistent with sialolithiasis in Wharton's duct. The stone was successfully removed via sialolithotomy. For the systematic review, an extensive search was conducted in PubMed, Embase, and Cochrane Library up to June 2025, using specific keywords. Initially, 262 studies were identified. After applying inclusion and exclusion criteria, six case reports were included in the final analysis. RESULTS: All selected studies described giant salivary stones located in Wharton's duct and/or the parenchyma of the submandibular gland, notably without associated pain. Computed tomography and ultrasonography were the most commonly used imaging modalities for diagnosis. In all cases, the primary treatment was sialolithotomy. CONCLUSIONS: This study explored a rare case report of an asymptomatic giant sialolith in Wharton's duct, and it includes a systematic review focused exclusively on asymptomatic giant sialoliths. It specifically addresses key characteristics, preferred imaging modalities, treatment strategies, and clinical considerations for managing this uncommon condition. REGISTRATION NUMBER: Prospero registration nº CRD420251076737.